Personalized treatment is better than one treatment fits all in the management of patients with mCRC: a consensus statement. (December 2014) - Yalcin, Suayib; Trad, Diaeddine; Kader, Yasser Abdel; Halawani, Hafez; Demir, Osman Gokhan; Mall, Riaz; Meshcheryakov, Andrey; Nasr, Fadi; Nosworthy, Adam; Osinsky, Dmitry; Tumanova, Assel; Turhal, Serdar; et al.
ABSTRACT : The VEGF- (bevacizumab) and EGFR- (cetuximab and panitumumab) targeting monoclonal antibodies have become integral components of the first-line treatment strategies for patients with metastatic colorectal cancer (mCRC). Increasingly combination chemotherapy, with or without a targeted agent, is being used to facilitate curative liver resection and improve survival rates in patients with initially unresectable but potentially resectable mCRC. Currently, the only selective marker for the treatment of patients with mCRC is tumor RAS mutational status. BRAF status is a strong prognostic indicator. Medical and clinical oncologists from Central Asia, Russia, the Middle East, Africa and Turkey reviewed data for the use of targeted agents in the treatment of patients with mCRC and have formed recommendations for the biological of choice first-line for patients with mCRC.